Contextualizing Islamic Inheritance Law in Indonesia: Addressing Negative Stigma - Bachri, Syabbul; Sudirman, Sudirman; Zuhriah, Erfaniah; Ramadhita, Ramadhita (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2024)
Islamic inheritance law is stigmatized due to its rigidity and conservativity. The rigidity and conservatism of Islamic inheritance can be seen in the view that Islamic inheritance rules cannot be changed or modified. In addition, the assumption of Islamic inheritance rules does not consider the social developments that occur over time. This research aims to explore how Islamic inheritance law is applied in Indonesia and how contextualization is carried out in response to existing stigma. This research employs a qualitative study with a normative juridical approach. The research data is derived from documents and texts on Islamic inheritance law and concrete cases of contextualization of Islamic inheritance law in Indonesia in different situations and contexts. The data are analyzed using descriptive interpretative techniques with the application of Amina Wadud's hermeneutics of tauhid. The research findings indicate that Islamic inheritance law in Indonesia has undergone contextualization, thus negating the negative stigma attached to Islamic inheritance. Contextualization is achieved by understanding and advocating Islamic inheritance law in the Indonesian context, reconstructing the basic concepts of Islamic inheritance law according to the Indonesian context, and promoting the resolution of inheritance conflicts through consultation and mediation. This research offers a model of inheritance division applied in Indonesia that is contextual and flexible based on Amina Wadud's hermeneutics of tauhid.